2020
DOI: 10.3389/fnbeh.2019.00283
|View full text |Cite
|
Sign up to set email alerts
|

Interoceptive Insular Cortex Mediates Both Innate Fear and Contextual Threat Conditioning to Predator Odor

Abstract: The insular cortex (IC), among other brain regions, becomes active when humans experience fear or anxiety. However, few experimental studies in rats have implicated the IC in threat responses. We have recently reported that inactivation of the primary interoceptive cortex (pIC) during pre-training, or the intra-pIC blockade of protein synthesis immediately after training, impaired the consolidation of auditory fear conditioning. The present study was designed to investigate the role of the pIC in innate and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 67 publications
1
10
0
1
Order By: Relevance
“…Alternatively, these data could reflect differences in the composition of glutamate receptors that potentially result in functional differences. Because the insular cortex is involved in negative affect, anxiety, fear memories and threat conditioning [31, 34, 35, 41, 63], and NMDA receptor adaptations are involved in synaptic plasticity in the insular cortex [64], these adaptations could in part underlie the hypervigilance phenotype observed in the context re-exposure test.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, these data could reflect differences in the composition of glutamate receptors that potentially result in functional differences. Because the insular cortex is involved in negative affect, anxiety, fear memories and threat conditioning [31, 34, 35, 41, 63], and NMDA receptor adaptations are involved in synaptic plasticity in the insular cortex [64], these adaptations could in part underlie the hypervigilance phenotype observed in the context re-exposure test.…”
Section: Discussionmentioning
confidence: 99%
“…The insular cortexr cortex and BNST form reciprocal projections [71, 72] and both regions contribute to affective behavioral measures in rodents [34, 35, 73] and humans [31]. Recent studies have shown that insular cortex/BNST circuitry are involved in negative affective measures associated with alcohol withdrawal in rodents [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muscimol (Sigma-Aldrich®), a selective GABA A agonist, was dissolved in sterile saline solution (0.9% NaCl). The dose of 0.5 µg/0.5 μ L was chosen based on previous studies that successfully inactivated the IC prior to aversive memory conditioning trainings (Berman et al, 2000;Casanova et al, 2016;Foilb et al, 2016;Koh & Bernstein, 2005;Rodríguez et al, 2020).…”
Section: Drug and Infusion Proceduresmentioning
confidence: 99%
“…Data are expressed as means + SEM. *p < 0.05.This figure has been modified from8 . Abbreviations: pIC = primary interoceptive cortex; Sal-Sal = saline injected on day…”
mentioning
confidence: 99%